Implementasi Scrum pada Pengembangan Point Of Sales pada UD.Maju Jaya Kopi Berbasis Website - Dwika Oktavian; Nuryanto Nuryanto; Pristi Sukmasetya (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
The data processing of goods at UD. Maju Jaya Kopi still uses the manual method, to find out the manager of the goods in the warehouse must check the location. The calculation of the entry of goods every month is still written in the book because there is no sales system yet, resulting in some incoming data not being appropriate so that they have to suffer or suffer losses. In every business there must be sales data so that it can know the entry and exit of goods received. So this coffee sales system was made in order to assist in sales at UD. Maju Jaya Kopi. This sales system uses the Java language program and Mysql database, The method developed to help facilitate the interests of running the sales system. The Scrum method is considered to be able to produce good software quality as desired by the user. Scrum itself is a software which uses agile that stands on a team, additional processes and software development that focuses on speed and is carried out by realizing the end result.